(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
The objective of this article is to identify and define assistive features that can be applied to a dress shirt to make this garment a more inclusive product for visually impaired people. For this purpose, a hybrid design methodology has been developed, based on the concept of inclusive design that presents features that allow easy access and handling by blind users. The hybrid methodology was developed in the Textile Materials Innovation course of the PPGMODA Udesc, based on the design methodologies proposed by Baxter (2011), Lobach (2001) and Bonsiepe (1984), as well as the fashion methodology of Montemezzo (2003). In terms of its nature, the research methodology is classified as qualitative and descriptive in terms of its objectives. Regarding the technical procedures for data collection, an online questionnaire was used through Google Forms, with five questions, three essay questions and two multiple choice questions, applied to 22 visually impaired men between 18 and 30 years old who wear dress shirts. The results show that enables the development of garments with more inclusive characteristics, contributing to easy access and manipulation by the visually impaired. Finally, the following resources are mentioned: (I) Braille labels, (II) QR CODE, (III) audiodescription.